2017
DOI: 10.18203/2320-1770.ijrcog20171545
|View full text |Cite
|
Sign up to set email alerts
|

Modified biophysical profile in antepartum fetal surveillance of high risk pregnancies

Abstract: Background: Fetal biophysical profile is a well-established method of antepartum surveillance in high risk pregnancy. Classical biophysical profile with all parameters (fetal breathing movements, fetal tone, fetal gross body movements, amniotic fluid volume and non-stress test) needs two phase testing by ultrasound and external Doppler monitor to record fetal heart rate, is more cumbersome, time consuming and expensive.Methods: This study was a prospective clinical study which consisted of 70 patients having p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
3
5
0
Order By: Relevance
“…Nine of the cases (81.8 %) had aberrant rBPP scores, while two of the cases (18.2 %) had normal rBPP scores. Our findings were compared to those of Yogitha V et al [2] and Soumya et al [8] in previous research. Three (7.1 percent) of the 42 patients with a normal rBPP score had birth asphyxia, while 39 (92.9 percent) had no birth asphyxia.…”
Section: Correlation Of Study Outcomes With Rbppsupporting
confidence: 56%
See 2 more Smart Citations
“…Nine of the cases (81.8 %) had aberrant rBPP scores, while two of the cases (18.2 %) had normal rBPP scores. Our findings were compared to those of Yogitha V et al [2] and Soumya et al [8] in previous research. Three (7.1 percent) of the 42 patients with a normal rBPP score had birth asphyxia, while 39 (92.9 percent) had no birth asphyxia.…”
Section: Correlation Of Study Outcomes With Rbppsupporting
confidence: 56%
“…The current study found that the incidence of abnormal study outcomes is higher than in previous studies (Table 6), and revealed that the incidence of abnormal study outcomes is linked to an abnormal rBPP score. [6] 8.8 ---Eden et al [7] 6.8 ---Nageotte et al [3] 5.6 ---Yogitha V et al [2] 30.1 100 88.8 -Soumya et al [8] The present study showed that scores of rapid Biophysical Profile have strong positive correlation with scores of biophysical profile (r 2 = 0.531, P=<0.001) and it was statistically significant. Similar results was reported by Prabhu AV et al [9] Sensitivity, specificity, Negative Predictive value and Positive predictive value was done between rBPP and BPP.…”
Section: Correlation Of Study Outcomes With Rbppsupporting
confidence: 48%
See 1 more Smart Citation
“…11 In a study by Sowmya et al, majority of the cases had birth weight between 2.5-3.5kgs, followed by 30% of the babies whose birth weight was between 1.5-2.4kgs. 13 Only 4.6% of the new-borns had APGAR score of 7 or less than 7 in this study. Three new-borns in this study were admitted to the NICU.…”
Section: Discussionmentioning
confidence: 48%
“…In the study of Nageotte et al 44% of cases had post-term, 11.8% of cases had hypertension, 23.8% of cases had IUGR, and 6.0% of cases had diabetes. 14 In a study by Eden et al (1988) 13 , 17.8% of cases had post-term, 27.9% of cases had hypertension, 16.6% of cases had IUGR, and 17.2% of cases had diabetes.…”
Section: Risk Factorsmentioning
confidence: 94%